STRATEGIES FOR TEACHING UNIVERSITY STUDENTS WITH ADHD: SCOPE REVIEW - Lucas Batista Ferreira; Rafaella Guilherme Gonçalves; Rejane Maria Paiva de Menezes; Soraya Maria de Medeiros (Universidade Federal do Paraná, 2024)
Objective: to map strategies for teaching university students with attention deficit hyperactivity disorder and identify recommended strategies for teaching these students pursuing a degree in nursing. Method: this is a scoping review. Conducted in December 2023 in six databases and the catalog of theses and dissertations. Results: the selection resulted in 14 studies. The mapped strategies were classified as general and active: extra time and flexible scheduling to conduct assessments and problem-based learning. In nursing, promoting better communication, organization, and prioritization of activities during clinical practice is necessary. Conclusion: it is essential to recognize that attention deficit hyperactivity disorder may be present in university students. Therefore, higher education institutions must reflect on inclusive teaching strategies for this target audience.